Pretreatment neutrophil‐lymphocyte ratio is not a significant prognostic factor in epidermal growth factor receptor‐mutant non‐small cell lung cancer patients treated with tyrosine kinase inhibitors - Sim, Sung Hoon (Thorac Cancer, 2015)
BACKGROUND: The neutrophil‐lymphocyte ratio (NLR) is a marker of poor prognosis in lung cancer patients. However, previous data have been based on an heterogeneous population of lung cancer patients and various treatments. In this study, we evaluate the prognostic value of NLR in an homogeneous population of epidermal growth factor receptor (EGFR)‐mutant non‐small cell lung cancer (NSCLC) patients. METHODS: We restrospectively evaluated the data of 250 NSCLC patients with EGFR mutations. All data are based on first‐line treatment. RESULTS: All tumors harbored in‐frame deletions in exon 19 or an L858R point mutation. Eighty‐five patients were treated with tyrosine kinase inhibitors (TKIs), while 165 received cytotoxic chemotherapy as first‐line treatment. Multivariate survival analysis revealed that the NLR was a significant prognostic factor for first‐line progression‐free survival (PFS) in the chemotherapy group (hazard ratio [HR] 1.882, 95% confidence interval [CI] 1.319–2.686, P = 0.001), but was not significant in the TKI group (HR 1.239, 95% CI 0.693–2.215, P = 0.469). The response rate (RR) to first‐line treatment was 76.5% in the TKI group and 29.5% in the chemotherapy group; however, the RR, according to the NLR (≤3 vs. > 3), was the same for both groups. CONCLUSIONS: The NLR was a significant prognostic factor in the chemotherapy group, but it did not affect either RR or PFS in EGFR‐mutant NSCLC patients treated with TKIs.